A new 3D-printed overtube system for endoscopic submucosal dissection: first results of a randomized study in a porcine model - Zizer, Eugen; Roppenecker, Daniel; Helmes, Felix; Hafner, Sebastian; Krieger, Yannick; Lüth, Tim; Meining, Alexander (Endoscopy, 2016)
Background and study aim: Endoscopic therapy of early malignant alterations can be difficult and cumbersome. Our research study group took advantage of new methods for rapid prototyping (i. e. 3D printing) to design and test an overtube system with two manipulator arms at the tip. Both arms can be steered independently from each other by a dedicated user platform. Methods: This animal study involved a randomized evaluation of the new overtube device for endoscopic submucosal dissection (ESD) compared with a conventionally performed ESD. In total, 12 ESDs in six pigs were performed. Six ESDs were performed in the stomach and six in the colon. Size (in cm2) of resected specimens, the time needed to perform endoscopic resection, and adverse events were assessed. Results: The overtube-assisted ESD was faster and therefore more effective than the conventional ESD technique (0.45 ± 0.24 cm2/min vs. 0.22 ± 0.11 cm2/min; P = 0.029). Only one adverse effect was recorded in the conventional group. Conclusions: The overtube-assisted ESD was feasible in an animal model. ESD can be performed more quickly and potentially more effectively with the newly designed overtube device compared with the conventional ESD technique.